Association study between BGLAP RS1800247-polymorphic variant and type 2 diabetes mellitus development among hypertensive and non-hypertensive Ukrainians - Chumachenko, Ya. D.; Kyrychenko, M. O.; Ramazanova, D. M.; Smiianova, M. V.; Harbuzova, V. Yu.; Ataman, O. V. (Zaporozhye Medical Journal, 2021)
The risk T2DM development depends on hereditary predisposition. According to the current data, skeleton enhances insulin gene expression in pancreatic β-cells as well as increases insulin sensitivity of adipocytes, myocytes and hepatocytes through the secretion of unOCN. The aim. To analyze the link between rs1800247 SNP and T2DM occurrence depending on the AH presence, as well as association between rs1800247 and systolic, diastolic, pulse, mean blood pressure among patients with diabetes. Materials and Methods. This study included 153 patients with diagnosed T2DM and 311 individuals without any carbohydrate metabolism disorders. Polymerase chain reaction-restriction fragment length polymorphism analysis (PCR-RFLP) was used for BGLAP rs1800247-genotyping. Logistic regression with interaction term “genotype × AH” was used to estimate the association between BGLAP rs1800247-genotypes and T2DM development under dominant, recessive, over-dominant and additive models of inheritance. Linear regression was performed to investigate the influence of minor C-allele on the arterial blood pressure. All calculations were performed using Statistical Package for the Social Sciences software (SPSS, version 22.0, Chicago, IL, USA). A value of P ˂ 0,05 was considered as significant. Results. No association was found between rs1800247 single nucleotide polymorphism and T2DM development neither in AH patients, nor in subjects without AH (Paint b > 0,05). There was no impact of rs1800247 genotypes on systolic, diastolic, pulse and mean blood pressure among patients with T2DM (P > 0,05). Conclusion. It was found the lack of association between rs1800247 SNP and T2DM development as well as blood pressure parameters. Further studies with extended groups of comparison are needed for the confirmation of results. This research was a part of the scientific project “Molecular-genetic and morphological features of lower limb tissues regeneration under conditions of chronic hyperglycemia” (0117U003926).